Application of the egogram pattern to clinical practice in the Department of Geriatric Dentistry - Karube, Yasuyo; Oguchi, Hitoshi; Morito, Mitsuhiko (Japanese Journal of Psychosomatic Dentistry, 2001)
Egograms are line graphs derived from the results of written questionnaires. They are used to indicate the psychological energy status of the ego. The ego, the driving force behind each individual, can readily be assessed on the basis of the egogram, enabling the subject to become more aware of his or her own ego, and thereby promoting self development. We perform this psychological test during clinical training from the latter half of year 5 to the first half of year 6 at dental school, using it to analyze the ego structure for purposes of comprehensive health care. In this study, we examined the results of egograms and explored new ways to use them for educational purposes. The study group comprised 179 students, for all of whom egograms were obtained. The students filled in the questionnaire after receiving basic explanations on interaction analysis and egograms. The resulting egogram pattern was explained to each subject, and their own behavior and execution patterns were commented on. The M type egogram was found to be most common, followed by the FC dominant type, inverse Nb type, and AC dominant type. Among the 29 possible patterns, 28 were found. The results showed that students receiving the same education are none the less characterized by all types of egogram patterns, indicating a basic difficulty of education. The use of egograms may be helpful in adapting education to the needs of individual students. Aside from discovering good or bad personality characteristics, or use in the diagnosis of disease, the egogram provides visual understandingof a subject's own behavior and execution patterns. We conclude that it is a valuable technique for use in understanding psychosomatic medicine.